CONCEPTUAL IDEAS AND GUIDELINES OF NORTH AMERICAN MODEL OF ADULT EDUCATION (Comparative Professional Pedagogy, 2024)
The article deals with conceptual ideas and guidelines of North American model of adult education. It is substantiated that North American model of adult education is based on the philosophical principles of liberalism, progressivism, behaviorism, humanism, radicalism, and constructivism. Liberalism has ancient roots and is based on the position that since the person is the real source of progress in society, it is necessary to ensure his/her rights and freedoms, providing equal access to education regardless of social status and well-being. The basic principle of liberal education is singled out, which is to develop a personality that meets the purpose of liberal education in ancient times – provision of education for citizens who can become active participants of a democratic society. It is proven that non-formal adult education should be continuous, focus on the development of intellectual abilities, be accessible to all layers of the population, and its content must meet their needs. It is found out that the historical roots of the philosophy of progressivism are associated with progressive political movement in society and education. Its basis is the concept of interaction between education and society, empirical theory of democratization of education. It is determined that behavioral philosophy, founded by John Watson, appeared in the USA in the early 20th century. Based on the theory of Pavlov's conditioned reflexes, its supporters (J. Watson, B. Sninner and E. Thorndike) considered personality as a set of behavioral responses to stimuli of the environment. It is identified that the purpose of adult education is the modification of a person’s behavior. It is proven that unlike behaviorists, representatives of humanistic philosophy (J. Brown, A. Maslow, M. Knowles, K. Rogers, etc.) considered a man to be independent, active, open to change and self-actualization. It is stressed that the founders of the radical trend, based on theories of anarchism, marxism, and socialism, considered education in general and adult education, in particular, as an important mechanism to achieve radical changes in society. Meanwhile, the social role of non-formal adult education was updated, because it required critical thinking and personal participation in these changes.
Keywords: the USA; adult education; liberalism; behaviorism; humanism; models of education